Papillary thyroid cancer: Genetic alterations and molecular biomarker investigations - Abdullah, Mardiaty Iryani; Mat Junit, Sarni; Khoon, Leong Ng; Jayapalan, Jaime Jacqueline; Karikalan, Barani; Hashim, Onn (Ivyspring International Publisher, 2019)
Papillary thyroid cancer (PTC) is the most prevalent form of malignancy among all cancers of the thyroid. It is also one of the few cancers with a rapidly increasing incidence. PTC is usually contained within the thyroid gland and generally biologically indolent. Prognosis of the cancer is excellent, with less than 2% mortality at 5 years. However, more than 25% of patients with PTC developed a recurrence during a long term follow-up. The present article provides an updated condensed overview of PTC, which focuses mainly on the molecular alterations involved and recent biomarker investigations.